2015
DOI: 10.4236/jectc.2015.54006
|View full text |Cite
|
Sign up to set email alerts
|

Development and Investigation of a Miniature Copper-Acetone Loop Heat Pipe with a Flat Evaporator

Abstract: The paper presents the results of development and investigation of a copper miniature loop heat pipe (LHP) with acetone as a working fluid. The device was equipped with a flat evaporator measuring 80 × 42 × 7 mm and vapor and liquid lines with an outside diameter of 3 mm, whose lengths were 145 mm and 175 mm, respectively. The LHP was tested at heat loads from 5 W to 60 W, different orientations in the gravity field and heat-sink temperatures from −40˚C to +50˚C. It is shown that the LHP retains its efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…For these tests, the LHP is positioned horizontally. Table 7 shows the different values of hsink for each sink temperature calculated based on the indicated volume flow rate in the study of Maydanik et al, [27] using the Dittus-Boelter correlation [59]. The convective heat transfer coefficient between the LHP and the ambient is hamb = 10 W/m.K and the ambient temperature Tamb = 20°C.…”
Section: Model Validation 61 Validation For the Evaporator And Vapor Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…For these tests, the LHP is positioned horizontally. Table 7 shows the different values of hsink for each sink temperature calculated based on the indicated volume flow rate in the study of Maydanik et al, [27] using the Dittus-Boelter correlation [59]. The convective heat transfer coefficient between the LHP and the ambient is hamb = 10 W/m.K and the ambient temperature Tamb = 20°C.…”
Section: Model Validation 61 Validation For the Evaporator And Vapor Temperaturesmentioning
confidence: 99%
“…In the second technology, the liquid flow is directed along the evaporator wall [18][19][20][21][22][23][24][25][26][27][28]. They are referred to as evaporators with Aside Compensation Chamber (AS-CC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially when the LHP works in the condition where the evaporator is higher than the condenser and compensation chamber, the gravity pressure difference will cause the increasing circulation resistance. At this point, the loop heat pipe often has problems such as over-temperature start-up, temperature fluctuations, which reduced the heat exchange capacity (Chen et al 2006;Maydanik et al 2015;Vershinin et al 2007;Filippeschi et al 2010;Chernysheva et al 2015). Chernysheva et al (2015) investigated the operating characteristics of a copper-water LHP to determine the effect of external factors such as the device orientation, in the range of heat loads from 20 to 600 W and at slopes from 0 to 60 o (see Fig.…”
Section: Anti-gravity Operation Capability Of Lhpmentioning
confidence: 99%
“…It is known that the cooling device is critical to promote high heat flux components' operation reliability, performance improvement and lifespan extension [1,2]. Lots of previous studies have shown that the development speed and scale of large application servers and data centers will largely be affected by the research and development progress of its cooling devices [3][4][5].…”
Section: Introductionmentioning
confidence: 99%